G113(P) A rare association of non haemolytic jaundice with simpson golabi-behmel syndrome 1 (SGBS1). (24th May 2017) - Mahmoud, SAS; Sansbury, F; Tunstall, O; Phillips, E; Buxton, C
Abstract : Aim: To our knowledge, there are no descriptions of infantile pyknocytosis (a condition in which abnormal red cells shape and size leads to neonatal haemolytic anaemia) as a feature in Simpson Golabi-Behmel Syndrome type 1 (SGBS1). We hereby present an infant to highlight this association. Methods: Case report and literature review. Results: A term macrosomic newborn boy, had some distinctive features such as macroglossia, macrostomia and a flattened nose. He had prolonged neonatal jaundice, secondary to non-immune haemolysis. A peripheral blood film and the pattern of his anaemia were in keeping with pyknocytosis. His macrosomia raised the possibility of Beckwith-Wiedemann Syndrome (BWS). Initial genetic testing, though, showed normal methylation of 11p15 at ICR1 and ICR2 (imprinting control regions 1 and 2). Subsequent review in the genetics clinic suggested a diagnosis of SGBS1. Next generation gene sequencing of GPC3 and GPC4 showed a 1 base pair deletion in GPC3, c.541del causing frameshift and a downstream stop codon, p. (Gln 181Serfs*), thus confirming the diagnosis of SGBS1. Further testing showed maternal inheritance. Discussion: Infantile pyknocytosis refers to the presence of small, irregular, distorted densely stained red blood cells. It is an uncommon cause of non-immune neonatal haemolysis. The condition usually resolves within few months of life. Simpson Golabi-Behmel Syndrome type 1 (SGBS1) is an Xlinked overgrowth condition with a variable presentation including macrosomia, craniofacial and other body features, and varying levels of intellectual disability. There is a risk of embryonal tumours in the liver, kidneys, adrenal glands and gonads. Affected males require screening in the form of abdominal USS for up until age 8 years. There are no reported associations between haematological abnormalities and SGBS1. While we cannot rule out that the presentation of these two rare conditions in the same child is coincidental, we report it to raise awareness of a possible link between the two conditions. Conclusion: In any infant with a diagnosis of infantile pyknocytosis and features of overgrowth, consider the possibility of SGBS1 or similar conditions. In an infant with SGBS1 and signs of haematological abnormalities, consider the possibility of infantile pyknocytosis.